2023
DOI: 10.3390/foods12112172
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Nutritional Characteristics and Volatile Flavor Substances of Yak Milk in Different Regions of Gannan

Guowu Yang,
Juanxiang Zhang,
Rongfeng Dai
et al.

Abstract: This study aimed to investigate the nutritional properties of yak milk in various areas of Gannan. The milk composition analyzer, automatic amino acid analyzer, and flavor analyzer were used to detect the conventional nutrients, amino acids, and volatile flavor substances of 249 yak milks in Meiren grassland, Xiahe grassland, and Maqu grassland (hereinafter referred to as Meiren yak, Xiahe yak, and Maqu yak) in the Gannan area. The results showed that the fat content of Meiren yak milk was significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…With the extension of aging time, n-amyl alcohol and heptanal, which have little effect on the flavor of fresh beef samples, become the key flavor components of 21-day dry-aged beef samples. Similar results were obtained by Yang et al [29]. In addition, 3-hydroxy-2-butanone, vinyl caproate, and 2-n-amylfuran are the key flavor components in the aging process.…”
Section: Determention Of Vfcssupporting
confidence: 88%
“…With the extension of aging time, n-amyl alcohol and heptanal, which have little effect on the flavor of fresh beef samples, become the key flavor components of 21-day dry-aged beef samples. Similar results were obtained by Yang et al [29]. In addition, 3-hydroxy-2-butanone, vinyl caproate, and 2-n-amylfuran are the key flavor components in the aging process.…”
Section: Determention Of Vfcssupporting
confidence: 88%
“…Due to its extreme living environment, yak milk has very high levels of nutrients (fat, protein, minerals), and especially a milk fat content as high as 6-8%. The triglycerides in milk fat will be hydrolyzed by lipase to produce free fatty acid [3,4], which will be converted into more volatile flavor substances, thus giving yak milk a unique flavor that is different from that of ordinary cow's milk. However, the dispersed location of grazing areas and the inconvenient transportation from production areas make it difficult to collect and transport fresh yak milk.…”
Section: Introductionmentioning
confidence: 99%
“…The unique highland environment has also endowed yak milk with distinctive physiological activity. Extensive research has reported on the health benefits of yak milk, including its role in enhancing tolerance to hypoxia, combating fatigue, providing antioxidant effects, and boosting immune function, which have significant potential for the development and application of yak milk [ 18 , 19 , 20 ]. However, due to the influence of geographical conditions, the milk yield of yaks is low, and most herdsmen still adopt artificial milking technology, resulting in low production efficiency and insufficient development and utilization of yak milk.…”
Section: Introductionmentioning
confidence: 99%